Announcement of First Successfully Pregnancy Following Abdominal Radical Trachelectomy in Viet Nam - Doan, Nghia Trong; Nguyen, Tien Van; Ta, Lieu Thanh; Vo, Nhi Tien Tan; Nguyen, Thu Duy; Phan, Thinh Xuan Minh; Nguyen, Phuc Huu (Asian Pacific Journal of Cancer Care, 2023)
Objectives: Abdominal radical trachelectomy (ART) is an alternative treatment for preserving fertility in selected patients with early - stage cervical cancer. This report to announce one case of successful conceive and gave birth following the abdominal radical trachelectomy. Materials and Methods: We have performed 12 cases of radical trachelectomy with pelvic lymphadenectomy in The Oncology Hospital of Ho Chi Minh city between January 2018 and December 2022. One of them has successful live birth after procedure about six months. Results: The characteristics of the 12 adult patients, who underwent radical trachelectomy, included stage IB1 disease in all cases, a mean age of 31 years (range, 29–41), and a median estimated blood loss of 100 ml (range, 70–150). No one needed adjuvant treatments after surgery, and all cases resumed normal menstruation postoperatively. There were no intraoperative complications. Transurethral Foley catheters were removed in all cases at postoperative days 02 – 04. Cervical stenosis was observed in one case. One case had successfully conceived and gave births following the abdominal radical trachelectomy. All patients remain disease-free after a median 3 - year follow-up. Conclusions: ART with pelvic lymphadenectomy is a feasible operation for selected women with early-stage cervical cancer cases who desire to preserve reproductive function. Menstruation and reproductive function might be preserved after bilateral uterine vessel ligation.